Job Scope Analysis Among Prosthetics and Orthotics Practitioners in Malaysia - Arifin, Nooranida; Hasbollah, Hasif Rafidee (Journal of Prosthetics Orthotics and Science Technology, 2023)
According to WHO and ISPO guidelines, three categories of personnel are involved in prosthesis and orthosis fabrication: prosthetists/orthotists; associate prosthetists and orthotists and prosthetics and orthotics technicians. It is important that they are competent and adequately trained. This is due to their responsibility in providing exemplary prosthetic and orthotics services to help users achieve mobility and elevate quality of life. To obtain information about the tasks performed on a job and the knowledge, skills, or abilities to perform those tasks, a practice analysis study is conducted. In this study, P&O companies in Klang Valley were invited to complete a survey to obtain information on professional background, domains, tasks, knowledge, skills etc. The survey questionnaires are adopted from the American Board for Certification in Orthotics, Prosthetics & Pedorthics, Inc. A total of 14 companies with 51 correspondents returned the survey. At the moment, the male practitioners dominate in P&O services (62%), most of the practitioners are between 25-34 years old, and mostly have <10 years of experience. In terms of patient distributions, adults are the highest (60%) followed by geriatric (20%) and pediatric (20%). The top three practice areas in orthotics are lower extremity (50%), spinal (21%) and upper extremity (15%), while for prosthetics are transtibial (30%), transfemoral (16%) and partial foot (11%). The top primary work performed are prosthetic and orthotic fabrication; clinical prosthetic and orthotic patient care; and education. Practitioners spent most of their time in these top three domains: patient assessment, formulation of the treatment plan and implementation of the treatment plan. These elementary findings of this study are useful for higher education and training providers in planning proper clinical and technical programmes for future and existing practitioners, also as support evidence for the policy maker in ensuring high quality provision of P&O services.